A technology assessment in acquiring geographic information system of Philip Morris Philippines for its Sales Department - Resoso, Michael Z. (University of the Philippines Diliman, 2009)
Part 1 of this report aims to discuss the objectives of the project as well as the significance of the assessment of acquiring Geographic Information System by Philip Morris Philippines for its Sales Department. The project also cited a background of the current situation of the company, the goals and objectives of the company with regards to finding a key technological solution that will fit the framework of the company's sales force. In achieving the goal of the company, the paper also discussed the methodologies of the research done in order to thoroughly review the capabilities of the said technology. Methodologies conducted in the study included library and internet research, quotation assessment of different GIS vendor in the country, and forecasting by analogy. Lastly, this paper also discussed the framework in conducting this project. The second part of the report tackles specific related information about the technology. It included a thorough review of related literature of the technology according to different experts of GIS. A discussion on innovation brought about by the technology and an evaluation of the acquisition of an enterprise and its analysis of the technology's return on investment is discussed as well. The study also talked about insights regarding the different articles that contributed to the benefits and success of the technology in having it integrated to the system of different industries. Part 3 of this report discussed the definition of GIS, what is the real deal with this technology? A thorough review of how the technology was utilized in the United States, the key industries that partake the integration of the technology to its system, and the success stories of these enterprises who committed to induce this technology in their business framework. A clear review of an analogous forecasting method was discussed in an attempt to compare and contrast the utilization of technology between the US and the Philippines. This attributed to the analysis and assessment of the report in integrating the technology in Philip Morris Philippines Sales Department. The best vendor to render the technology to the company was conducted and was evaluated in this part. Finally, the last part contains the conclusions and recommendation based on the initial findings of the study that included the gathered results and analysis, this project clearly showed to top management that acquiring GIS technology would be beneficial to the company's sales force team in order to exceed the expected objectives and goals the company. Acquisition of the GIS technology was highly recommended based on the technology assessment in this project.